Probing the final-stage progenitor evolution for Type IIP Supernova 2017eaw in NGC 6946. Issue 2 (19th February 2019) - Rui, Liming; Wang, Xiaofeng; Mo, Jun; Xiang, Danfeng; Zhang, Jujia; Maund, Justyn R; Gal-Yam, Avishy; Wang, Lifan; Zhang, Tianmeng
Abstract: We presented a detailed analysis of progenitor properties of type IIP supernova 2017eaw in NGC 6946, based on the pre-explosion images and early-time observations obtained immediately after the explosion. An unusually red star, with M F814W = −6.9 mag and m F606W − m F814W = 2.9 ± 0.2 mag, can be identified at the SN position in the pre-discovery Hubble Space Telescope ( HST ) images taken in 2016. The observed spectral energy distribution of this star, covering the wavelength of 0.6–2.0 μ m, matches that of an M4-type red supergiant (RSG) with a temperature of about 3550 K. These results suggest that SN 2017eaw has a RSG progenitor with an initial mass of 12 ± 2 M⊙ . The absolute F814W-band magnitude of this progenitor star is found to evolve from −7.2 mag in 2004 to −6.9 mag in 2016. Such a dimming effect is, however, unpredicted for an RSG in its neon/oxygen burning phase when its luminosity should modestly increase. The spectrum of SN 2017eaw taken a few hours after discovery clearly shows a narrow Hα emission feature blueshifted by ∼160 km s −1 . This narrow component disappeared in the spectrum taken two days later, suggesting the presence of a circumstellar material (CSM) shell (i.e. at a distance of <2.1–4.3 × 10 14 cm). Combining the inferred distance with the expansion velocity of the CSM, we suggest that the progenitor of SN 2017eaw should have experienced violent mass-loss at about 1–2 yr prior to explosion, perhaps invoked by pulsational envelop ejection. This mechanism may help explain its luminosity decline in 2016 as well as the lack of detections of RSGs with relatively higher initial mass as progenitors of SNe IIP.